2004
DOI: 10.1128/jcm.42.3.1367-1369.2004
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Basidiobolomycosis in an Immunocompetent Woman

Abstract: Basidiobolomycosis is a chronic subcutaneous infection of the trunk and limbs due to Basidiobolus ranarum.The disease is well known in tropical areas, although recent cases of gastrointestinal basidiobolomycosis have also been reported in Arizona. We describe a young immunocompetent women who had presented with eosinophilia and lung infiltrates. She subsequently died, and diagnosis of disseminated basidiobolomycosis was made on the basis of histological features at autopsy. CASE REPORTA nonsmoking, 40-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 15 publications
0
57
0
1
Order By: Relevance
“…In the cutaneous form, the portal of entry is believed to be through the skin, after insect bites, scratches and minor cuts. It is most common in young children as a disease of the skin and subcutaneous tissues, involving the thighs and buttocks (Bigliazzi et al, 2004). Most cases have been reported in tropical and subtropical climates, mainly in Indonesia and East and West Africa (Antonelli et al, 1987;de Leó n-Bojorge et al, 1988;Bittencourt et al, 1991;Scholtens & Harrison, 1994;Sugar, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the cutaneous form, the portal of entry is believed to be through the skin, after insect bites, scratches and minor cuts. It is most common in young children as a disease of the skin and subcutaneous tissues, involving the thighs and buttocks (Bigliazzi et al, 2004). Most cases have been reported in tropical and subtropical climates, mainly in Indonesia and East and West Africa (Antonelli et al, 1987;de Leó n-Bojorge et al, 1988;Bittencourt et al, 1991;Scholtens & Harrison, 1994;Sugar, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, the genus Basidiobolus of the order Entomophthorales produces deeply invasive fungal infections (Wasim Yusuf et al, 2003). Basidiobolus ranarum is an environmental saprophyte found worldwide and isolated from decaying vegetation, foodstuff, fruits and soil, as well as from the gastrointestinal tracts of reptiles, amphibians, fish and insectivorous bats (Bigliazzi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal (GIB) (Hussein et al, 2007), retroperitoneal (Finelli et al, 1997;Nazir et al, 1997) and pulmonary (Bigliazzi et al, 2004) basidiobolomycosis have been reported in the medical literature. Surgery and prolonged antifungal therapy are usually required for treatment (van den Berk et al, 2006).…”
Section: Introductionmentioning
confidence: 99%